Effect of decreasing inorganic N:P ratio on the plankton community - INN:PP - Mari Vanharanta; Mariano Santoro; Cristian Villena-Alemany; Jonna Piiparinen; Hans-Peter Grossart; Matthias Labrenz; Kasia Piwosz; Kristian Spilling (PANGAEA, 2025)
The Baltic Sea has been affected by eutrophication for several decades with the result of a gradual increase of oxygen minimum zones at the sea floor and release of phosphate from sediments. This has generated a decreasing inorganic nitrogen:phosphorus (N:P) ratio and excess phosphate remaining after the spring bloom. In the present study, a 17-days experiment was performed on June 2021 at the Tvärminne Research Station (Gulf of Finland, Northern Baltic Sea) where the effects of the decreasing ratio of dissolved inorganic nitrogen and phosphorus on the planktonic community were investigated in 12 in-situ mesocosms. Temperature, dissolved oxygen concentration and salinity were determined in situ, whilst water samples were collected during the whole duration of the experiment using a Limnos sampler (Hydro-Bios, Kiel), transported to the laboratory and processed for measurements of dissolved inorganic, organic and particulate nutrients, extracellular enzymatic activities, bacterial production, bacterial abundance, pigments fluorescency and concentration, eukaryotic organisms and prokariotyc cell and filament counts. Dissolved inorganic nutrients (nitrate, nitrite, ammonium, phosphate and silica) were determined according to Grasshoff et al. (1999). Concentrations of dissolved organic carbon and total dissolved nitrogen were determined. Dissolved organic nitrogen (DON) was calculated as difference between total dissolved nitrogen and dissolved inorganic nitrogen. Total dissolved phosphorus concentration was determined according to Koistinen et al. (2017). Dissolved organic phosphorus was calculated as difference between total dissolved phosphorus and dissolved inorganic phosphorus. Concentrations of particulate organic carbon (POC) and particulate organic nitrogen (PON) were also determined. The concentration of particulate organic phosphorus (POP) was measured according to Solórzano & Sharp (1980) with slight modification by Koistinen et al. (2017). Particulate organic elemental ratios POC:PON:POP were calculated on a molar basis. Extracellular enzymatic activities were determined according to Baltar et al. (2016). Bacterial production was determined as thymidine and leucine incorporations according to Fuhrman and Azam (1982), Smith and Azam (1992) and Kirchman et al. (1985). Chlorophyll-a was extracted from biomass according to Jespersen and Christoffersen (1987). Chlorophyll-a and Phycocyanin relative fluorescences were also measured. Filamentous cyanobacterial counts were determined after being stained with DAPI (4',6-diamidino-2-phenylindole) and counted using epifluorescence microscopy according to Andersen and Throndsen (1995). Picocyanobacterial and heterotrophic bacterial counts were determined according to Gasol and Del Giorgio (2000). Aerobic anoxygenic phototrophic bacteria were determined using epifluorescence microscopy with infrared emission method (Piwosz et al. 2022). Picoeukaryotes counts were determined via flow cytometry. Counts of adults, nauplii and egg sacks of Copepoda, Amphibalanus sp. and larvae, Evadne sp., Podon sp., Bosmina sp., Synchaeta sp. and Keratella quadrata were manually identified via images created using a flatbed scanner.